A career workshop's effect on vocational identity, career indecision and self efficacy of 10th graders - Caligiuri, Judith A., author; Daly, Joseph, advisor; Kees, Nathalie, committee member; Feller, Richard, committee member; Turner, Joseph G., committee member (Colorado State University. Libraries, 1996)
The purpose of this study was to determine a career workshop's effect on the vocational identity, career indecision, and career self efficacy of 10th grade high school students: Twelve research questions were tested to determine the workshop's effect on the three dependent variables: vocational identity, career indecision, and career self efficacy. The primary independent variable was the activities in the workshop. The study also examined whether gender, ethnicity, or academic ability interacted with the treatment workshop on students' vocational identity, career indecision, and career self efficacy. Three standardized instruments were used to measure the variables. The My Vocational Situation, vocational identity scale (Holland, Daiger, & Power, 1980) was used to measure vocational identity. The Career Decision Scale, career indecision scale (Osipow, Carney, Winter, Yanico, & Koschier, 1976) was to used to measure career indecision. The Occupational Self Efficacy Scale, confidence rating scale, (Betz & Hackett, 1981) was used to measure career self efficacy. The 171 subjects in this study were from two rural high schools in Colorado. Eighty seven subjects formed the treatment group sample. Eighty four students formed the control group sample. Major findings in the study indicated the treatment group increased significantly in vocational identity on the MVS post test. Career indecision was significantly lower for the treatment group, as measured by the CDS post test. Career self efficacy did not show a significant degree of change. Boys and girls in the treatment group changed significantly on post test adjusted scores in vocational identity and career indecision. Hispanics in the treatment group did not show a significant degree of change from the Hispanics in the control group on any of the dependent variables. Students of high, middle, and low academic ability did show a significant increase in vocational identity, and a decrease in career indecision. Some limitations exist. Career workshops using other assessments, other blocks of time, or alternate activities with subjects in a different demographic area may find different results. Therefore, generalizability is limited. However, indications supported the use of a career workshop intervention with high school 10th graders to increase vocational identity, and decrease career indecision. More research on the construct of self efficacy is encouraged.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Career development; Vocational guidance; Career education; Self-esteem